Palatability, digestibility of various constituents and nitrogen retention in Marwari sheep offered Salicornia bigelovii biomass and Cenchrus ciliaris straw mixed diet - BOHRA, H C; PATEL, A K; KAUSHISH, S K (The Indian Journal of Animal Sciences, 2011)
Feeding and metabolism trials were conducted to assess palatability of Salicornia bigelovii biomass (SB) and digestibility of its various constituents in sheep. SB (50%) diet was fairly palatable in sheep. When the sheep was offered different diets having SB and Cenchrus ciliaris (CC) straw using cafeteria system, the sheep always preferred the diet that contained minimum level of Salicornia biomass. Daily dry matter intake in SB (75%) and CC diet did not vary. However, daily water intake as well as urine out put was considerably high in SB (75%) fed animals due to high sodium chloride content of the SB diet. Dry matter, cell contents and crude protein digestibility of SB (75%) diet was high, whereas, in CC diet the digestibility coefficients for organic matter, cell-wall constituents, acid detergent fibre and hemicelluloses were on the higher side. Incorporation of SB (75%) in CC diet increased salt load, resulted in high water intake. The major advantage of SB incorporation in the CC based diet was seen in the form of high crude protein intake and its digestibility. This was also apparent in the nitrogen balance where the sheep fed on SB (75%) showed a positive (+1.22±0.150 g day–1) nitrogen balance whereas the animals fed on CC alone exhibited a negative balance (–4.71±0.874 g day–1). The findings emanated from this study show the prospects of using Salicornia diet in future for increasing protein status of the animals foraging upon salinity affected desert rangelands.